161k views
3 votes
Madison created this solved this proof. She wants to know if she solved it correctly. After looking at the proof, decide whether she solved the proof correctly. If she did not explain why it is incorrect and correct it.

Given : 4(5n + 7)-3n = 3(4n - 9) Prove: n=-11
Statements Reasons
4(5n + 7) - 3n = 3(4n - 9) Given
20n + 28 - 3n = 12n - 27 Distributive Property
17n + 28 = 12n - 27
Simplify
5n + 28 = -27 Addition Property of Equality
5n = -55 Multiplication Property of Equality
n = -11 Division Property of Equality

1 Answer

2 votes

answer: madison correctly solved the equation, but step 3 should be subtraction property of equality.

work: to start off, madison correctly used the distributive property in step one. She also correctly simplified in step two. Step three is where she messed up. somehow, she put "Multiplication Property of Equality" when she actually used the subtraction property of equality. step 3 and step 4 were still correctly solved, though.

User Bholtbholt
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.